2021
DOI: 10.5014/ajot.2021.046169
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for the Treatment of Anxiety Disorders: A Scoping Review

Abstract: Importance: Virtual reality in head-mounted displays (HMD-VR) may be a valuable tool in occupational therapy to address anxiety. Findings from the virtual reality exposure therapy (VRET) literature may facilitate translation of HMD-VR to occupational therapy psychosocial practice. Objective: To explore how HMD-VR has been used to treat anxiety through VRET and could be translated to occupational therapy. Data Sources: We searched seven electronic databases for articles published b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…The t tests showed significant differences in the total score between technology commitment (t 28 =2. 19…”
Section: Pretreatment Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…The t tests showed significant differences in the total score between technology commitment (t 28 =2. 19…”
Section: Pretreatment Scoresmentioning
confidence: 99%
“…Studies show promising results for the treatment of social anxiety disorders and fear of public speaking [ 15 , 16 ] by including virtual humans that may be controlled by a therapist [ 17 ]. A comparable effectiveness of VRE in the treatment of anxiety disorders compared to in vivo treatment has been successfully identified in the broad spectrum of anxiety-related disorders [ 18 , 19 ] and specific phobias [ 20 , 21 ]. Deterioration rates are likely to occur randomly and could not be traced back to the application of VRE therapy in a meta-analysis with several treatment approaches for anxiety [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A wide review of VR studies [32] published between 2000 and 2020 and indexed in major electronic databases (a total of 28 studies analyzed) confirms the effectiveness of using various programs based on VR technology for the treatment of many negative mental conditions, including post-traumatic stress disorder, specific phobias, and social anxiety.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, Shah et al [ 28 ] study indicated the effectiveness of virtual reality exposure therapy in reducing stress and depression in patients suffering from mood disorders. Donnelley et al [ 29 ] indicated that head-mounted VR is a valuable device for occupational therapy to simulate the environments in which patients with anxiety disorders participate. Evoking presence via multi-sensory features and body representation may enhance the effectiveness.…”
Section: Discussionmentioning
confidence: 99%